Status Gizi, Jenis dan Lama Pemakaian Alat Kontrasepsi Pil, Suntik 1 Bulan dan Suntik DMPA dengan Gangguan Menstruasi - Nunung Hardiyanti Enggoe; Luh Putu Ruliati; Lewi Jutomo; Noorce Christiani Berek; Idawati Tresno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the relationship between nutritional status, type and duration of contraceptive pills, 1-month injection and Depo Medroxy Progesterone Acetate (DMPA) injection with menstrual disorders in women of childbearing age in Kupang City. The method used is a quantitative method with a cross-sectional design. The sampling technique was simple random sampling with stratified random sampling. The results showed that there was a relationship between nutritional status and menstrual disorders with a value of (P = 0.000), type of contraception and menstrual disorders (P = 0.000), duration of contraceptive use and menstrual disorders (P = 0.001). In conclusion, there is a relationship between nutritional status, type, and duration of use of contraceptive pills, 1-month injections and DMPA injections with menstrual disorders. Keywords: Menstrual Disorders, Types of Contraception, Duration of Use, Nutritional Status